Assessing IS research impact - Niederman, Fred; Kevin Crowston; Koch, Hope; Krcmar, Helmut; Powell, Philip; E. Burton Swanson (Communications of the Association for Information Systems, 2015)
Based on the International Conference on Information Systems’ (ICIS) 2013 senior scholars’ forum, this paper shares insights on IS research impact assessment. We define research impact as conducting research that makes a difference to individuals, businesses, industries and societies. While assessment groups like AACSB (the Association to Advance Collegiate Schools of Business) want scholars to make an impact, sometimes they operationalize impact in ways that may encourage scholars to pursue research goals tangential to making a difference. The purpose of this paper is to stimulate thinking in the IS community on creating research assessment techniques that encourage our scholars to make a difference.